Retakāful operation in Malaysian practice: issue and solutions - Megat Laksana, Nan Noorhidayu; Abdul Aziz, Akhtarzaitie (IIUM Press, International Islamic University Malaysia, 2017)
Retakāful is an important financial tool through which takāful operators pay an agreed amount from takāful fund to the retakāful operators in order to get protection against loss or unexpected risk. Retakāful is an alternative for takāful operators to reinsure their risk. Some of the concepts and practices in reinsurance are relevant and acceptable in the practice of retakāful. This study attempts to discuss and examine retakāful operation as implemented by retakāful operators in Malaysia. Three retakāful operators in Malaysia had been selected by the researcher in order to get a clearer understanding of the implementation of retakāful operation models which are ACR Retakāful SEA Berhad, MNRB Retakāful Berhad and Munich Re Retakāful Berhad. In addition, this study attempts to analyse the fiqhī issues in retakāful operation.